DINAMIKA AKTIVITAS BELAJAR SISWA DAN KINERJA GURU DALAM PEMBELAJARAN MEMBACA PERMULAAN BERBANTUAN MEDIA FLASHCARD DI KELAS II SEKOLAH DASAR - Muhamad Hafid Nugraha; Nurani Hadnistia Darmawan; Hilman Hilmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of the learning process, as reflected in student activity and teacher performance, constitutes one of the determining factors in the success of early reading instruction, in addition to test results. This study aims to describe the dynamics of student learning activity and teacher performance during the implementation of flashcard media in early reading instruction in Grade II of SD Negeri Cikaret. This study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles. The subjects of this study were one teacher and 20 second-grade students of SD Negeri Cikaret, selected using a total sampling technique. Data were collected through student activity observation sheets, teacher performance observation sheets, and field notes. The data were then analyzed using descriptive-quantitative and qualitative methods through triangulation. The results showed that student learning activity increased from the Sufficient category (60%) in Cycle I to Very Good (90%) in Cycle II. Meanwhile, teacher performance improved from 65% (Sufficient) to 90% (Very Good). The field notes revealed a shift in student attitudes from passive and hesitant to active, courageous, and confident, in line with the refinement of actions involving the enlargement of card size, the rearrangement of seating positions, shared reading activities, and the reinforcement of feedback. Therefore, it can be concluded that the implementation of flashcard media proved capable of fostering student learning engagement while simultaneously enhancing the teacher's skill in managing early reading instruction.